The Identification of Euglenids (Euglenophyceae, Euglenophyta) from the Peat Waters of Palangka Raya, Indonesia - Chaidir Adam; Agus Haryono (Pandawa Institute, 2023)
The aim of this study was to identify and describe the Euglenids (Euglenophyceae, Euglenophyta) from the peat waters of Palangka Raya, Central Kalimantan, Indonesia. This study revealed that 8 species of Euglenids were found in the study sites which belong to 3 genera, namely Euglena, Lepocinclis, and Phacus. The Euglenid species identified include Euglena gracilis G.A. Klebs 1883, Euglena mutabilis F. Schmitz 1884, Lepocinclis acus (O.F.Müller) B.Marin & Melkonian 2003, Lepocinclis ovum (Ehrenberg) Lemmermann 1901, Lepocinclis spirogyroides B.Marin & Melkonian 2003, Phacus cordatus (Pochmann) Zakryś & Lukomska 2015, Phacus helikoides Pochmann 1942, and Phacus orbicularis Hübner 1886. The eight Euglenid species found in this study have never been reported before, thus these findings provide additional new data regarding algae diversity in peat waters of Central Kalimantan, Indonesia.